Age variation of the concentration of toxicants in organs and tissues of sheep in the zone of technogenic pollution - A. K. Mikhailenko (Юг России: экология, развитие, 2015)
Sheep living in the area of technogenic pollution have heavy metals accumulation and changes in histological structure of organs and tissues in ontogenesis as well.